Health promotion intervention delivered by trained community health workers (CHWs) for obesity prevention and control among adult people: a scoping review protocol - Yogi Fitriadi; Wahyu Danawati; Adi Heru Sutomo (BMJ Open)
Introduction Obesity is one of the most common diseases and is the main risk factor for the occurrence of other non-communicable diseases, such as hypertension, diabetes, heart disease and cancer. Obesity can be prevented and controlled, especially by adopting healthy behaviours, such as increased physical activity and healthy dietary patterns. The delivery of health promotion interventions by trained community health workers (CHWs) can be applied to obesity prevention and control based on the culture and local context. Our study aimed to map the health promotion interventions delivered by trained CHWs in the context of obesity prevention and control in community settings.Methods This scoping review (ScR) was conducted using the methodologies introduced by Arksey and O’Malley. The search strategy was conducted on electronic databases, such as MEDLINE via PubMed, Scopus, Cochrane, ProQuest, medRxiv and Clinicaltrial.gov, from 2010 until 2022 by entering the appropriate keywords. Afterwards, the title, abstract and full text were screened independently by two researchers in accordance with the inclusion and exclusion criteria. Then, the data were charted, extracted, collated, summarised and reported.Ethics and dissemination In this ScR, research ethics was unnecessary because this work synthesised evidence from pre-existing literature only. The results of this ScR were published in peer-reviewed journals and presented at scientific conferences. We disseminated the results using graphs, images, tables, discussions and a plain language summary.